2015
DOI: 10.1002/2014jd022279
|View full text |Cite
|
Sign up to set email alerts
|

Processing of aerosol particles within the Habshan pollution plume

Abstract: The Habshan industrial site in the United Arab Emirates produces a regional-scale pollution plume associated with oil and gas processing, discharging high loadings of sulfates and chlorides into the atmosphere, which interact with the ambient aerosol population. Aerosol particles and trace gas chemistry at this site were studied on two flights in the summer of 2002. Measurements were collected along vertical plume profiles to show changes associated with atmospheric processing of particle and gas components. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Alternatively, higher tail concentrations from ultra-giant sizes of 20-50 µm are recorded during SF4 compared with SF1. This is in line with the previous suggestion of higher ultra-giant CCN loading from local pollution and dust aggregation over the southwest compared with the eastern regime (Semeniuk et al, 2015).…”
Section: Aerosol Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…Alternatively, higher tail concentrations from ultra-giant sizes of 20-50 µm are recorded during SF4 compared with SF1. This is in line with the previous suggestion of higher ultra-giant CCN loading from local pollution and dust aggregation over the southwest compared with the eastern regime (Semeniuk et al, 2015).…”
Section: Aerosol Measurementssupporting
confidence: 93%
“…Furthermore, the ambient aerosols appear to be naturally hygroscopic as suggested by their deliquescence and growth to sizes of ∼ 7 µm (peak concentrations) at cloud base. This is more pronounced over the southwestern region where mineral aggregates are formed from sea salt and sulfate particles emitted from local oil refineries (Semeniuk et al, 2015). While the C-C process remained inactive in all observed cases, it is hypothesized that the presence of large dust and pollution aggregates causes a "natural competition effect" as reported by Tessendorf et al (2021) based on their aircraft observations from the Queensland Cloud Seeding Research Program (QCSRP).…”
Section: Implications For Hygroscopic Cloud Seedingmentioning
confidence: 64%
See 1 more Smart Citation
“…Based on the results from different sampling sites, dispersed‐OM and dumbbell structures are not common mixing structures (Figure ) and tend to transform into OM‐coating and core‐shell structures (Figure ). We conclude that OM‐coating and core‐shell structures are important indicators of particle aging in clean and polluted air (Figure ), except when close to the specific emission sources [ Semeniuk et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results from different sampling sites, dispersed-OM and dumbbell structures are not common mixing structures ( Figure 6) and tend to transform into OM-coating and core-shell structures (Figure 8). We conclude that OM-coating and core-shell structures are important indicators of particle aging in clean and polluted air ( Figure 6), except when close to the specific emission sources [Semeniuk et al, 2015]. Bauer et al [2013] suggested that the knowledge of realistic mixing structures of individual particles is necessary to explain their hygroscopicity, cloud condensation nucleus activity, and optical properties in field measurements and modeling simulations.…”
Section: Developing a Conceptual Framework And Understanding Its Atmomentioning
confidence: 90%